2005
DOI: 10.1111/j.1740-0929.2005.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationship of feed efficiency traits of bulls with growth and carcass traits of their progeny for Japanese Black (Wagyu) cattle

Abstract: Genetic parameters for feed efficiency traits of 740 Wagyu bulls and growth and carcass traits of 591 of their progeny, and the genetic relationship between the traits of bulls and their progeny were estimated with the residual maximum likelihood procedure. The estimations were made for the test periods of 140 days (77 bulls), 112 days (663 bulls) and 364 days (591 steer progeny). Feed efficiency traits of bulls included feed conversion ratio (FCR), phenotypic residual feed intake (RFI phe ) and genetic residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
26
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 18 publications
(45 reference statements)
13
26
4
Order By: Relevance
“…The present value (0.28±0.23) of genetic correlation between ADG and MWT was lower than value of 0.37±1.24 estimated by Aktar et al (2011), however, Hoque et al (2005 showed extremely higher result (0.96±0.09) than in the present study. The estimated heritability for ADG (0.30±0.10) simply agreed to the value observed by Hoque et al (2005) in Japanese Black bulls.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 69%
See 1 more Smart Citation
“…The present value (0.28±0.23) of genetic correlation between ADG and MWT was lower than value of 0.37±1.24 estimated by Aktar et al (2011), however, Hoque et al (2005 showed extremely higher result (0.96±0.09) than in the present study. The estimated heritability for ADG (0.30±0.10) simply agreed to the value observed by Hoque et al (2005) in Japanese Black bulls.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 69%
“…The correlation between RFI with BWT of the progeny was close to zero (0.06±0.18) and well comparable to the 0.08±0.22 established by Aktar et al (2011). Hoque et al (2005) established a correlation of bull RFI with body weights of their progeny were -0.33 at starting the test and -0.61 at finishing. Thus their conclusion was that a favorable negative genetic correlation between RFI and body weights of the progeny indicated the selection for lower RFI (higher feed efficiency) of bulls would lead to an increase in body weights of their progeny.…”
Section: Heritability and Genetic Correlationssupporting
confidence: 53%
“…The positive correlation between F:G and RFI indicates that selection for either of these measures of feed efficiency will, on average, improve the other (Arthur et al, 2001b;Hennessy and Arthur, 2004). Positive phenotypic correlations ranging from 0.60 to 0.72 between RFI and DMI calculated with different breeds of cattle have been reported (Herd and Bishop, 2000;Hoque et al, 2005;Nkrumah et al, 2007). Similarly, in the present study the correlation between RFI and DMI indicates that Table 6 Characterization of metabolic hormones and metabolites at the end of the test period in animals with low, medium, and high residual feed intake.…”
Section: Discussionmentioning
confidence: 89%
“…Dry matter conversion to body weight gain is a useful indicator of quality of feed and the ability of an animal to convert feeds to body tissues (Hoque et al, 2005). Dietary treatments used in the present study affected the feed conversion ratio (FCR).…”
Section: Feed Intake and Growth Performancementioning
confidence: 99%